Insights into tribofilm formation on Ti-6V-4Al in a bioactive environment: Correlation between surface modification and micro-mechanical properties. (15th March 2022) - Qi, J.; Guan, D.; Nutter, J.; Wang, B.; Rainforth, W.M.
Abstract: Ti-6Al-4V has been used as a surgical implant material for a long time because of its combination of strength, corrosion resistance and biocompatibility. However, there remains much that is not understood about how the surface reacts with the environment under tribocorrosion conditions. In particular, the conditions under which tribofilms form and their role on friction and wear are not clear. To evaluate the complicated nature of the dynamic surface microstructural changes on the wear track, high resolution transmission electron microscopy (TEM), scanning transmission electron microscope (STEM) and electron energy loss spectroscopy (EELS) have been used to characterise the structure and chemical composition of the tribofilm. Detailed analysis of the formation and structure of the tribofilm and the metal surface deformation behaviour were studied as a function of applied potential and the role of proteins in the lubricant. For the first time, graphitic and onion-like carbon structures from wear debris were found in the testing solution. The presence of carbon nanostructures in the tribocorrosion process and the formation of the tribofilm leads to an improved tribocorrosion behaviour of the system, in particular a reduction in wear and friction. A detailed, quantitative, analysis of surface deformation was undertaken, in particular, the geometrically necessary dislocation (GND) density was quantified using precession electron diffraction (PET). A clear correlation between applied potential, tribofilm formation and the surface strain was established. Statement of significance: The formation of tribofilm and microstructure modification of the Ti-6Al-4V surface during tribocorrosion in a physiological environment is not fully understood. In particular, the correlation between microstructural changes and electrochemical conditions is not clear. This study presents a detailed investigation of the structure and chemical composition of tribofilms at the nanoscale during tribocorrosion tests in simulated body fluid and gives a detailed and quantitative description of the evolved surface structure. A clear correlation between applied potential, tribofilm formation and the surface strain was established. Moreover, particular attention is paid to the wear debris particles captured from the lubricating solution, including nanocarbon onion structures. The implications for tribocorrosion of the alloy in its performance as an implant are discussed. Graphical abstract: Image, graphical abstract